Use of Water Hyacinth and Fermented Fruit Waste as BSF (Black Soldier Fly) Media on The Quality of BSF Maggot Flour - F. Ardiansyah; E. Susanto; Wahyuni (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
This study aims to assess BSF maggot flour’s quality using water hyacinth growing media and fermentedfruit waste using EM-4 and molasses. Held a total of 70 g of baby maggot was in the temple for 15 days.Eldest the feed used using fermented water hyacinth and fermented fruit waste with four treatmentsconsist of P0= 0% fermented water hyacinth+ 100% fermented fruit waste, P1= 25% fermented waterhyacinth+ 75% fermented fruit waste, P2= 50% fermented water hyacinth+ 50% fermented fruit waste,and 75% fermented water hyacinth+ 25% fermented fruit waste. The design of the experiment uses acompletely randomized design (CRD). The results showed that substitution of feeding 25% fermentedwater hyacinth+ 75% fermented fruit waste influenced the yield of BSF maggot flour (P <0.05), and therewas no effect on the pH quality of Maggot BSf flour (P> 0.05). The best results’ (substitution of feeding25% fermented water hyacinth+ 75% fermented fruit waste) has proximate content of dry matter89%, ash 11%, crude protein 35.5%, crude fat 12%, calcium 7%, nitrogen-free extract material 7%,metabolist energy 2939.64 kcal/ 100 g.